Sie sind auf Seite 1von 4

Summary on Relations and Functions Relations

A relation is defined as a set of ordered pairs, that obeys a particular rule. A Set of ordered pairs is a relation. This is also called a Mapping. E.g. y = x + 3 this is an equation. x x + 3 this is the relation or mapping. Where x = {x: -2 x3} This means the values of x are {-2,- ,!, ,2,"# Hence the relation { $-2, %,$- ,2%, $!,"%,$ ,&%,$2,'%,$",(%# The set of all first components of the ordered pair is called the Domain. The set of all second components of the ordered pair is called the Range.

Types of relation
One to One relation one element in the domain is connected to one element in the range. Many to One ) Many elements in the domain are connected to one element in the range. One to Many One element in the domain is connected to many elements in the range. Many to Many Many elements in the domain are connected to many elements in the range.

Functions
* relation that is either a +ne to +ne or a many to one is called a function. ,onsider the relation x 2x + 5 is a function and can be -ritten as f: x 2x +5 or f(x) = 2x + 5 -hich is read .the function of x is 2x +5 . E ample !f f(x) = x2 + 7x 5 find the "a#$es of Steps i. f(2) ii. f(-%)

i.

&o find f(2) s$'stit$te x= 2 into the ex(ression x2 + )x * 5 f(x) = x2 + )x * 5 f(2) =( 2)2 + () / 2) * 5 = + + %+ * 5 = %3

&o find f(-%) s$'stit$te x= -% into the ex(ression x2 + )x * 5 f(x) = x2 + )x * 5 f(-%) = (-%)2 +() / - %) * 5 =%-)*5 = -%% The in!erse of a function ii. The inverse of a function f-%(x) 0this means interchanging / for y and y for /1 * function has an inverse if and only if the function is a one to one mapping The inverse of a function maps the output $range% of a function bac2 to its input $domain%.

e.g.

3et f$/% 4 {$ ,&%, $2,5%, $", !%#6 this is a set of ordered pairs $/, y% Then f- $/% 4 {$&, %, $5,2%, $ !,"%#6 no- the inverse -ill be $y, /%

e.g.

7f f: x +x * 3, determine the inverse of the function. Solution x +x * 3 this means y = +x * 3 x=+y * 3 x + 3 = +y Steps . 3et y 4 the function 2. 7nterchange / for y and y for /. &herefore f-%(x) = ". 9a2e y the sub:ect of the formula. determine an e/pression for g-%(x)

e.g.

8iven g(x) 4

solution y4 $let y 4 the function%

x4
x(2y * 5 ) = 3y + 2 2xy * 5x = 3y + 2 2xy * 3y = 2 + 5x y(2x * 3) = 2+ 5x y=

$interchange y for / and / for y% $cross multiply% $e/pand% $,ollect all the y terms on side of the equation% $factorise the y% $9a2e y the sub:ect of the formula%

&herefore g-%(x) =

e.g.

;etermine the inverse of f(x)=

and hence so#"e the e,$ation

ii. solution y4

<tate the real value of x, for -hich cannot be in the domain of f(x)

x= x(y + 5) = 3y + 5 xy + 5x = 3y + 5 xy * 3y = 5 * 5x y$/ - "% 4 ' ) '/ y4

therefore f-%(x) 4

hence so#"e the e,$ation =ence means to use -hat -as found to find the ans-er. >?. The solution of the given equation is found by finding the value of f- $2%. f-%(x) 4

f-%(2) 4

= ii. To find the real value of x -hich cannot be in the domain@ to find the value of / -hich -ill ma2e the function undefined. Steps . 3et the denominator equals Aero 2. <olve for x -et x + 5 = . x = -5 Therefore the real value of / -hich cannot be in the domain is -'

---------------------------------------------------------------------------------------------------Composite function

8iven t-o functions f(x) and g(x). We obtained the composite function fg (x) "y su"stituting g(x) for x in f(x).

! fg(x) / gf(x) e.g. The functions f and g are defined by f(x) = ) + x and g(x) = 2x * 3. Write and e/pression forB i. fg(x) ii. gf(x)

solution fg(x) = f(2x * 3) f(2x * 3 ) = ) + ( 2x * 3) = ) + 2x * 3) = + + 2x &herefore fg(x) = + + 2x i. ii. gf(x) = g()+ x) g() + x)= 2() + x) * 3 = %+ + 2x * 3 = %% + 2x &herefore gf(x) = %% + 2x

The functions f(x) = solution i. h(x) = h $2% = =

, g(x) =

and h(x) =

find i. gh$2%

ii. fg$!%

To find gh(2) <teps &. Cist find h$2% '. The value you get for h$2% (. <ubstitute it for / in g.

ii. To find fg(.) g$!% = =+ f(+) = = &herefore fg(.) = <teps . Cist find g$!% 2. The value you get for g$!% ". <ubstitute it for / in f.

g( ) = = &herefore gh(2) =